Effective myofibroblast dedifferentiation by concomitant inhibition of TGF-β signaling and perturbation of MAPK signaling - Kosla, Jan; Dvorakova, Marta; Dvorak, Michal; Cermak, Vladimir (European journal of cell biology, 2013)
Fibrotic diseases are a group of pathologies with high incidence and mortality. Despite extensive research efforts, effective therapies are still not available. Understanding the molecular mechanisms driving the onset, progression and possible resolution of fibrosis is a prerequisite to the development of successful therapies. The central role of the TGF-β pathway and myofibroblasts in the pathogenesis of fibrosis is now generally accepted. The possible mechanisms of myofibroblast elimination or dedifferentiation, on the other hand, are still almost uncharted territory. Here we show that sustained expression of some components of MAPK signaling pathway (PDGFB, Ha-Ras(G12V) or the transcription factor EGR4) in primary chicken embryo dermal myofibroblasts results in a loss of autocrine TGF-β signaling and suppression of the myofibroblastic phenotype, characterized by the loss of alpha smooth muscle actin fibers and a substantial reduction in the production of extracellular matrix. Detailed analysis of the possible molecular mechanisms employed by EGR4 revealed FOXG1, BAMBI, NAB1, NAB2 and DUSP5 genes forming an EGR4 regulated network counteracting autocrine TGF-β signaling. We have also found that a combination of chemical inhibition of TGF-β signaling and perturbation of MAPK signaling with phorbol ester mimics the anti-fibrotic effects of PDGFB, Ha-Ras(G12V) and EGR4.
Keywords: Myofibroblast; signální transdukce; Cell Dedifferentiation; Actins; Microarrays; FOXG1; Chick Embryo; PDGFB; Signal Transduction; aktiny; kuřecí embryo; Myofibroblasts; TGF-β; forbolové estery; Phorbol Esters; Mitogen-Activated Protein Kinases; Transforming Growth Factor beta; transformující růstový faktor beta; zvířata; EGR4; mitogenem aktivované proteinkinasy; Ha-Ras(G12V); dediferenciace buněk; myofibroblasty; Animals